On the nature of rethinking prophetic literature. Stirring a neglected stew (A response to David L. Petersen) - Linville, James Richard (The journal of Hebrew scriptures, 1999)
David L. Petersen's 1997 paper, "Rethinking the Nature of Prophetic Literature" posits a five-fold typology of prophetic literature and prophetic roles: (1) divinatory chronicles about seers; (2) vision reports concerning seer/visionaries; (3) prophetic speech from prophets; (4) legends about men of God; (5) prophetic histories, attributed to intermediaries with no formal title. Petersen critiques other scholars for stereotyping prophets as formal speakers or poets, viewing prophetic literature too often as the actual words of prophets, and reducing its diversity to a single message. Petersen makes a number of valid points, especially his call for an interdisciplinary dialogue. Yet, he himself is dismissive of many approaches in the "methodological stew" that he considers "uninformed". His typology is supported by ambiguous evidence, and he works with an uncritically studied premise that the Hebrew Bible reflects accurate data about prophets. Similar objections can be raised concerning his complaints about the prejudgments. My critique is based on a fundamentally different historical paradigm than that of Petersen. Cross-cultural comparisons cannot reliably describe the social institution of prophecy, although other types of social scientific research may provide heuristic tools for study in different directions. The biblical portrait of 'classical' prophecy needs analysis as the construction of a later era. The literary qualities of the texts also deserve attention. Perceptual role theory, as opposed to the role theory employed by Petersen, may provide a link between literary and historical research into the manufacturers of the biblical portrait. The required dialogue is much more eclectic than Petersen's paper would allow.